Use of project based learning (PJBL) learning model to improve learning outcome of cognitive learning and skills of student science on biodiversity material at SMAN 1 Peukan Bada Aceh Besar - Maulizar Maulizar; Hafnati Rahmatan; M Ali S (Jurnal Edubio Tropika, 2018)
This research aims to determine the improvement of learning outcomes, students' science process skills, and relationships with science process skills learned through Project Based Learning model of the material of biodiversity in SMA N 1 Peukan Bada. This research was conducted on August 14 to September 7, 2016. The method used is a quasi-experimental method with pretest-posttest control group design. Thepopulation in this study were all high school students in grade 1 Peukan Bada XMIA amounted to 83 students in two classes, namely samples X MIA grade 2 as the experimental class numbered 20 students and 3 X MIAclass as control class numbered 20 students. This research instrument uses test and skill observation skill of science process. Analysis of the test data using independent sample t-test with SPSS 20.0 for windows atsignificant level of 0.05 for the difference in learning outcomes in the control class and experimental class.Scientific process skills are analyzed by percentage, relationship of learning result and science process skill using correlation formula. The results showed that (1) the results of student learning has increased significantly (t hit. 9.362 t tab. 2,021) at the significant level of 5% (ɑ = 0.05). The conclusion in this research is learning by using PjBL model can improve student learning outcomes in SMA N 1 Peukan Bada Aceh Besar District.Keywords: Model Project Based Learning, Learning Outcomes and Biodiversity.